2019
DOI: 10.1093/cid/ciz630
|View full text |Cite
|
Sign up to set email alerts
|

Generating the Evidence for Typhoid Vaccine Introduction: Considerations for Global Disease Burden Estimates and Vaccine Testing Through Human Challenge

Abstract: Typhoid fever has had a major impact on human populations, with the causative pathogen Salmonella enterica serovar Typhi implicated in many outbreaks through history. The current burden of disease is estimated at 11–18 million infections annually, with the majority of infections located in Africa and South Asia. Data that have been used to estimate burden are limited to a small number of blood-culture surveillance studies, largely from densely populated urban centers. Extrapolating these data to estimate disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Microbial challenge studies are useful for providing proof of concept for therapeutic interventions and can substantially reduce the time needed to reach phase 3 studies, as has been shown for malaria and typhoid vaccine development. 74 , 75 , 76 …”
Section: Controlled Human Infection Modelmentioning
confidence: 99%
“…Microbial challenge studies are useful for providing proof of concept for therapeutic interventions and can substantially reduce the time needed to reach phase 3 studies, as has been shown for malaria and typhoid vaccine development. 74 , 75 , 76 …”
Section: Controlled Human Infection Modelmentioning
confidence: 99%
“…Often cited barriers to vaccine development include limited investment, with only $3.7 M of new R&D funding globally in 2018 18 , an excess of candidate antigens and delivery systems 19 , the questionable predictive capacity of pre-clinical animal models 20,21 , lack of good correlates of protection and a defined target product profile 22 , the costs and challenge of large-scale efficacy studies in disease endemic countries coupled with the high prevalence of asymptomatic infections 23,24 and a fragmented pipeline for translational research 25 . As has been found with other diseases [26][27][28][29][30][31][32][33] , the incorporation of a controlled human infection model (CHIM) into the vaccine R&D pipeline can overcome many of these issues.…”
mentioning
confidence: 99%
“…The current burden of disease is estimated at 11-18 million infections annually, with the majority of infections located in Africa and South Asia. 8 Kim et al reported 180940 cases in 303 identified outbreaks caused by infection with S. typhi and Salmonella enterica serovar paratyphi A or B (S. paratyphi). The size of the outbreaks ranged from 1 to 42564.…”
Section: Discussionmentioning
confidence: 99%